Determinants of subjective quality of life among older married adults in Poland - Chełchowska, Milena (Studia Demograficzne, 2020)
In recent decades, the issue of life quality and its determinants has been increasingly discussed in the scientific literature. One of the key determinants of subjective well-being is the fact of being in a relationship (formal or not) as well as its quality. The results of analyzes for other countries show that people who have a partner have a higher subjective well-being than people who do not live with their spouse, while divorced people have the lowest (and the highest level of depression). In addition to being in a relationship, its quality is also important: people more satisfied with marriage declare greater well-being than those less satisfied. The aim of the study is to analyze quality of life (expressed in terms of well-being and depression) among older people in Poland, putting emphasis on their individual (e.g. age, sex, health status, level of education) and household (financial situation) characteristics. Importantly, the analysis takes into account the quality of the marriage approximated by the satisfaction with marriage declared by both spouses separately. For the purposes of this study I use data of ‘Social Diagnosis’ study carried out in 2015 in Poland. The final sample was limited to partnered older people aged 65+. Basic individual socio-demographic and economic as well as household characteristics were controlled for. The results show that older partnered men in Poland have higher subjective well-being than older partnered women. Also, older partnered men report significantly higher levels of marital satisfaction than older partnered women do. Moreover, it should be underlined that higher levels of marital satisfaction among older spouses may be beneficial for their own quality of life expressed by well-being and depression. Thus, better opinion about marriage may increase subjective well-being and decrease depression level. However, this relationship is different for older partnered men and women. Positive relationship between marital satisfaction and well-being is stronger for partnered women when subjective well-being is taken into account and for men when well-being is understood as depression level.